De Nereidas catulianas a peces golondrinos: metamorfosis textual en la "Columbeida" (1585) de Julio César Stella - Díaz Gito, Manuel Antonio (Ágora : estudos clássicos em debate, 2015)
With the exception of an earlier poem by Lorenzo Gambara, Columbeis (Rome,1585) by Italian humanist Giulio Cesare Stella is the first fully epic Latin poem about Columbus’s heroic deeds. This article examines the textual and contextual adaptation of an Argonautic passage by Catullus, in which the Nereids play the leading role (Catul.64.1-15), into a passage by Stella where Columbus’s sea-crossing is described (Col. 1.47-51).